2002
DOI: 10.1037/0012-1649.38.4.564
|View full text |Cite
|
Sign up to set email alerts
|

Differences in early parent-child conversations about negative versus positive emotions: Implications for the development of psychological understanding.

Abstract: The authors examined whether the quality and content of everyday parent-child conversations about negative emotions are the same or different from everyday talk about positive emotions. Extensive longitudinal speech samples of 6 children and their parents were analyzed for several critical features when the children were between 2 and 5 years of age. Results showed that children and parents talked about past emotions, the causes of emotions, and connections between emotions and other mental states at higher ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
132
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(155 citation statements)
references
References 84 publications
9
132
1
4
Order By: Relevance
“…Emotion is important, therefore, because it is not only thinking about emotion (which has been the focus of much theory-ofmind research) but thinking with emotion about self and others that stimulates early social understanding. This is one reason why in our studies (see as well as others (Lagattuta & Wellman 2002), relational influences are especially apparent in children's conversations about and comprehension of negative emotional events. Constraint and cooperation are both conceptually provocative experiences for young children.…”
Section: Wittgensteinian Developmental Investigationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Emotion is important, therefore, because it is not only thinking about emotion (which has been the focus of much theory-ofmind research) but thinking with emotion about self and others that stimulates early social understanding. This is one reason why in our studies (see as well as others (Lagattuta & Wellman 2002), relational influences are especially apparent in children's conversations about and comprehension of negative emotional events. Constraint and cooperation are both conceptually provocative experiences for young children.…”
Section: Wittgensteinian Developmental Investigationsmentioning
confidence: 97%
“…These include Rogoff's (1990) constructivist view of the appropriation of social cognition in shared activity, Nelson's (1996) portrayal of the growth of the linguistically mediated mind, and the inquiry of theory-of-mind researchers into social influences on psychological understanding (e.g., Lagattuta & Wellman 2002). Social developmentalists have also been concerned with the influence of social interaction on mental representation.…”
Section: Wittgensteinian Developmental Investigationsmentioning
confidence: 99%
“…Similarly, Lagattuta and Wellman (2002) found that children talked about past emotional experiences, discussed the causes of emotions, and asked open-ended questions at higher rates when talking about negative than about positive feelings (see also Stein & Miller, 1993). Children in Lagattuta and Wellman's (2002) study also talked more about the relationships between negative emotions and other mental states than between positive emotions and mental states (for a review of similar findings with adults, see Taylor, 1991). In contrast, when discussing positive emotions, both children and adults focused on people's current, on-going emotional attitudes (such as "like" or "love") rather than on more discrete emotional states (such as "happy").…”
Section: B Evidence From Other Developmental Domainsmentioning
confidence: 98%
“…Several studies conducted with parents of TD children have shown that parents display more supportive reactions (e.g., helping to solve the problem that caused the child's distress) in daily life than non-supportive reactions (e.g., feeling embarrassed by an emotional display) (e.g., Eisenberg, Fabes, & Murphy, 1996;McElwain, Halberstadt, & Volling, 2007;Perry, Calkins, Nelson, Leerkes, & Marcovitch, 2012). During emotion-related conversations, mothers and fathers emphasize positive and negative emotions (e.g., Lagattuta & Wellman, 2002;Ontai & Thompson, 2002) and they explain (e.g., Denham & Auerbach, 1995;Garner, Dunsmore, & Southam-Gerrow, 2008) or ask questions about the causes and consequences of emotions (e.g., Denham & Auerbach, 1995;Lagattuta & Wellman, 2002;Ruffman, Slade, & Crowe, 2002). These studies suggest that parents who react in a supportive way and/or discuss emotions in the family may foster their children's emotional and social development, notably their Theory of Mind development (e.g., McElwain et al, 2007, Ruffman et al, 2002 or their emotional regulation (e.g., Perry et al, 2012;Shewark & Blandon, 2015).…”
Section: Introductionmentioning
confidence: 99%